Characterisation of a High-Power Impulse Magnetron Sputtered C/Mo/W wear resistant coating by transmission electron microscopy - Sharp, Jo; Müller, Itzel Castillo; Mandal, Paranjayee; Abbas, Ali; Nord, Magnus; Doye, Alastair; Ehiasarian, Arutiun; Hovsepian, Papken; MacLaren, Ian; Rainforth, W. Mark (Surface & coatings technology, 2019)
Thin films of C/Mo/W deposited using combined UBM/HIPIMS sputtering show 2–8 nm clusters of material richer in Mo and W than the matrix (found by EDS microanalysis), with structures that resemble graphitic onions with the metal atoms arranged regularly within them. EELS microanalysis showed the clusters to be rich in W and Mo. As the time averaged power used in the pulsed HIPIMS magnetron was increased, the clusters became more defined, larger, and arranged into layers with amorphous matrix between them. Films deposited with average HIPIMS powers of 4 kW and 6 kW also showed a periodic modulation of the cluster density within the finer layers giving secondary, wider stripes in TEM. By analysing the ratio between the finer and coarser layers, it was found that this meta-layering is related to the substrate rotation in the deposition chamber but in a non-straightforward way. Reasons for this are proposed. The detailed structure of the clusters remains unknown and is the subject of further work. Fluctuation electron microscopy results indicated the presence of crystal planes with the graphite interlayer spacing, crystal planes in hexagonal WC perpendicular to the basal plane, and some plane spacings found in Mo2C. Other peaks in the FEM results suggested symmetry-related starting points for future determination of the structure of the clusters. •The microstructure of a hybrid C-Mo-W magnetron/HIPIMS coating was studied by TEM.•The structure is of 3-10 nm metal carbide clusters in an amorphous carbon matrix.•The clusters arranged in layers; which modulate in density over 4–6 layers.•EELS reveals the carbon is graphitic and the clusters contain metals and carbon.•FEM shows amorphous structures and structures related to [W/Mo]C and graphite.